2015
DOI: 10.1016/j.bbamem.2015.02.007
|View full text |Cite
|
Sign up to set email alerts
|

A refined atomic scale model of the Saccharomyces cerevisiae K+-translocation protein Trk1p combined with experimental evidence confirms the role of selectivity filter glycines and other key residues

Abstract: Potassium ion (K+) uptake in yeast is mediated mainly by the Trk1/2 proteins that enable cells to survive on external K+ concentration as low as a few μM. Fungal Trks are related to prokaryotic TRK and Ktr and plant HKT K+ transport systems. Overall sequence similarity is very low, thus requiring experimental verification of homology models. Here a refined structural model of the Saccharomyces cerevisiae Trk1 is presented that was obtained by combining homology modeling, molecular dynamics simulation and exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 52 publications
1
19
0
Order By: Relevance
“…4) contains an M1 helix, a pore helix (MP), the ion-selectivity filter motif (black asterisks in Fig. 4), and helices M2a and M2b [44]. To facilitate understanding of the identified mutations, we set out to generate a homology model of S. cerevisiae Trk1p ( Sc Trk1p) (Additional file 1: Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4) contains an M1 helix, a pore helix (MP), the ion-selectivity filter motif (black asterisks in Fig. 4), and helices M2a and M2b [44]. To facilitate understanding of the identified mutations, we set out to generate a homology model of S. cerevisiae Trk1p ( Sc Trk1p) (Additional file 1: Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A refined structural model of Trk1 and experimental validations showed that glycines within the selectivity filter are important for protein function and correct folding/membrane targeting [44]. Specifically, mutating these glycines into bulky residues leads to a growth defect in low concentrations of KCl.…”
Section: Discussionmentioning
confidence: 99%
“…Key residues in that structure have been identified. For example, four Gly within the selectivity filter are thought to be involved in the binding of the cation, and Leu 949 or Lys1147 have been shown to be important in the structure and functioning of the transport process (Haro & Rodriguez‐Navarro, , ; Zayats et al, ). Zayats and coworkers not only published a refined version of the model but also included experimental evidence supporting the structure of Trk1 (Zayats et al, ).…”
Section: The Trk Potassium Uptake Systemmentioning
confidence: 99%
“…For example, four Gly within the selectivity filter are thought to be involved in the binding of the cation, and Leu 949 or Lys1147 have been shown to be important in the structure and functioning of the transport process (Haro & Rodriguez‐Navarro, , ; Zayats et al, ). Zayats and coworkers not only published a refined version of the model but also included experimental evidence supporting the structure of Trk1 (Zayats et al, ). A significant difference between ScTrk1 and ScTrk2, or most of the Trk proteins belonging to this family, is the presence of a long intracellular segment (second cytosolic segment) in ScTrk1, whose possible function in regulatory processes has not been definitively established yet.…”
Section: The Trk Potassium Uptake Systemmentioning
confidence: 99%
“…Crystal structure of a similar type of transporter, TrkH from Vibrio parahaemolyticus , demonstrates a selectivity filter for K + and Rb + over Na + and Li + (Cao et al, 2011 ). Atomic scale and molecular dynamics modeling of Trk1 from S. cerevisiae confirmed homology with HKT transporters and revealed essential role of glycine residues within potassium selective filter region of the protein, sodium ions were inhibiting for K + transport (Zayats et al, 2015 ). However, still more experimental evidence is required and heterologous expression systems may also be useful for solving the puzzle.…”
Section: Ion Transport Systems Of Yeast Cellsmentioning
confidence: 99%